2017
DOI: 10.1097/inf.0000000000001681
|View full text |Cite
|
Sign up to set email alerts
|

Severe Lower Respiratory Tract Infection Caused by Human Bocavirus 1 in an Infant

Abstract: We report a case of human bocavirus 1 (HBoV1) bronchiolitis that led to life-threatening respiratory failure in a 9-month-old boy with no other pathogens detected. The virus-specific diagnosis was confirmed with the detection of HBoV1 DNA in respiratory samples and both DNA and IgM and IgG to HBoV1 in serum samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…It is frequently detected in young children experiencing acute respiratory tract illness. The symptoms range from the mild symptoms of the common cold to severe pneumonia and bronchiolitis that can be life threatening (4)(5)(6)(7)(8)(9). Notably, recent studies have shown that HBoV1 infection is a significant cause of pediatric community-acquired pneumonia (CAP); when the respiratory secretions of pediatric patients with CAP were assessed for various infections using nonbiased transcriptome sequencing (RNA-seq) and viral mRNA detection analyses, HBoV1 was detected in 18.6% of children with CAP caused by unknown pathogens compared with 2.2% of control subjects, and HBoV1 alone appeared to be responsible for the disease in 2.1% of cases of CAP (10,11).…”
mentioning
confidence: 99%
“…It is frequently detected in young children experiencing acute respiratory tract illness. The symptoms range from the mild symptoms of the common cold to severe pneumonia and bronchiolitis that can be life threatening (4)(5)(6)(7)(8)(9). Notably, recent studies have shown that HBoV1 infection is a significant cause of pediatric community-acquired pneumonia (CAP); when the respiratory secretions of pediatric patients with CAP were assessed for various infections using nonbiased transcriptome sequencing (RNA-seq) and viral mRNA detection analyses, HBoV1 was detected in 18.6% of children with CAP caused by unknown pathogens compared with 2.2% of control subjects, and HBoV1 alone appeared to be responsible for the disease in 2.1% of cases of CAP (10,11).…”
mentioning
confidence: 99%
“…Furthermore, serological studies have revealed that HBoV1 acute infections occur most often in early childhood, with HBoV1 IgG seroconverting at a median age of 1.9 years and reaching a seroprevalence of 80% by 6 years of age [24]. Several clinical cases have shown severe or even life-threatening respiratory tract diseases due to HBoV1 infection in children [10,[15][16][17][18][19]29]. However, it should be kept in mind that, due to HBoV1 long-term persistence in the upper airways, the virus is frequently co-detected with other respiratory pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…These states of affairs at first may seem contradictory; however, HBoV1 has been shown to remain in the nasopharynx for several weeks and even months, thereby causing clinically false polymerase chain reaction (PCR) diagnoses. Moreover, life-threatening and even fatal HBoV1 infections have been reported [15][16][17][18][19]. The definition and diagnosis of acute HBoV1 respiratory tract infection is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand many viruses do exhibit similar clinical pictures and cannot be clinically differentiated (Pavia, 2011). Although, the exact clinical picture of acute HBoV1 infection remains to be defined, in several case reports severe and even life-threatening respiratory tract diseases due to HBoV1 in children have been disclosed (Ursic et al, 2011;Körner et al, 2011;Edner et al, 2012;Jula et al, 2013;Ursic et al, 2015;Moesker et al, 2015;Eskola et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact clinical picture of an acute HBoV1 infection remains unclear, the most frequently described clinical symptoms of HBoV1-associated infection include fever, cough, rhinitis and wheezing (Jartti et al, 2012;Qui et al, 2017). Several clinical case reports have shown acute HBoV1 infection in life-threatening respiratory tract infections (Körner et al, 2011;Ursic et al, 2011;Edner et al, 2012;Ursic et al, 2015;Eskola et al, 2017).…”
Section: Introductionmentioning
confidence: 99%